HUBUNGAN SISTEM PEMBUANGAN LIMBAH RUMAH TANGGA DAN KONTRUKSI SUMUR GALI DENGAN SYARAT FISIK AIR DI WILAYAH KERJA PUSKESMAS SALO TAHUN 2020 - Rinancy, Hariet; Puteri, Ade Dita (Universitas Pahlawan, 2021)
According to data from WHO ((World Health Organization) every person in developed countries needs between 60-120 liters of water per day. According to Permenkes No. 416 / MENKES / PER / IX / 1990 water used for daily purposes is of the highest quality. Dug wells meet health requirements including in Indonesia. Dug wells provide water from a layer of soil that is relatively close to the surface of the soil. Therefore, dug wells are easily contaminated through seepage. The aim of this study was to determine the relationship between household sewage systems and construction. dug wells with physical water requirements in the working area of the Salo Health Center in 2020. The design used in this study is descriptive analytic with a cross sectional approach. Random sampling is 91 houses, and the data analysis used is univariate t and bivariate. The results of the bivariate analysis show that there is a significant relationship between the household waste disposal system and the physical requirements of water in the work area of the Salo Health Center in 2020 with a p value of 0.003, there is a significant relationship between dug well construction and the physical requirements of water in the work area of the Salo Health Center in 2015 with the p. value 0.001. The community should always monitor and improve the physical conditions that allow it to be fixed so that the infiltration of waste water does not enter the dug wells and the quality of dug well water is maintained.